2012
DOI: 10.1111/opn.12007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying modifiable factors to improve quality for older adults in hospital: a scoping review

Abstract: Registered nurses have a leadership role to ensure safe quality care for older people in hospital. This leadership role can be framed in interventions that focus on fixing the fit between what older people need and what the hospital environment provides. Modifiable factors for improvement are within the scope and competency of the registered nurse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Hospital admission can adversely impact the older person's quality of life, functional status, ability to return home and sometimes their survival (Parke, Hunter, Bostrom, Chambers, & Manraj, ). Hospitals have been criticised for failing to meet the unique and complex needs of older people (Baumbusch, Leblanc, Shaw, & Kjorven, ), and in the fast‐paced, unfamiliar environment, those with cognitive impairment are at higher risk (Heath, Sturdy, & Wilcock, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hospital admission can adversely impact the older person's quality of life, functional status, ability to return home and sometimes their survival (Parke, Hunter, Bostrom, Chambers, & Manraj, ). Hospitals have been criticised for failing to meet the unique and complex needs of older people (Baumbusch, Leblanc, Shaw, & Kjorven, ), and in the fast‐paced, unfamiliar environment, those with cognitive impairment are at higher risk (Heath, Sturdy, & Wilcock, ).…”
Section: Introductionmentioning
confidence: 99%
“…Parke et al . () also identified a range of specialised consultation teams for older hospitalised adults, including one led by a geriatrician trained in geriatric psychiatry and including a specialised geriatric liaison nurse. The team focused on providing psychogeriatric liaison for medical patients.…”
Section: Resultsmentioning
confidence: 99%
“…Specialised care units and specialist consultation teams have been associated with improved care for older people in hospital. One scoping review identified eight different specialised care units for older people that commonly included interdisciplinary specialised geriatric resources on designated units (Parke et al 2012). None were focused on patients with dementia, although the Hospital Elder Life Program (HELP) is aimed at reducing delirium in hospitalised older adults and an evaluation found significant improvement in the degree of cognitive impairment among patients with impairment at admission (Inouye et al 1999).…”
Section: Models Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Awareness has increased that the outcome of a hospitalization does not depend solely on the condition of elderly adults, but also on the quality of specific geriatric programs . Delivering high‐quality geriatric care in hospitals requires programs such as Senior‐Friendly Hospitals and Nurses Improving Care for Healthsystem Elders . Receiving high‐quality care can prevent the onset of geriatric syndromes, including impaired mobility, falling, delirium, incontinence, and polypharmacy .…”
mentioning
confidence: 99%